Writing scientific interpretation between prohibition and leave | كتابة التفسير العلمي بين المنع والإجازة - Ulin Nuha (Al-Zahra : Journal for Islamic and Arabic Studies, 2017)
This research aims to understand the method of scientific interpretationwhich was prepared by the Committee of Quranic Correction in the Ministry ofReligious Affairs of Indonesia. The used method is inductive method,particularly by collecting scientific data from the interpretation of theinterpretation, especially the scientific explanation. The researcher extracted hismethod from interpretation and extrapolation over the book.This research reveals that the definition of scientific interpretation is due tothe definition of general interpretation of the term, and then allocated in the senseand from which.